The Effect of Different Commercial Probiotics on the Diversity and Density of Sea Water Plankton in the Experiment Tub - Mizar Desrialdi; Boedi Setya Rahardja; Endang Dewi Masithah (Universitas Airlangga, 2020)
The presence of plankton in pond ecosystems fluctuates. Phytoplankton needs nutrients to support their growth. The higher the nutrient content in the waters, the greater the abundance of phytoplankton. The increased abundance of phytoplankton will stimulate the growth of zooplankton. One of the causes of changes in ecosystems in waters is caused by water waste that comes from the rest of the feed and feces and in the form of ammonia or nitrite and nitrate. Water quality is a critical factor in the cultivation process. As a preventative measure, the decrease in water quality in waters is by giving probiotic bacteria. This study aims to obtain information about the effect of giving different commercial probiotics to the diversity and density of seawater plankton in the experimental bath. The method used in this research is descriptive method with a Completely Randomized Design (CRD) as an experimental design. The treatments used are different types of commercial probiotics, with as many as six replications. The main parameters observed were the diversity and density of seawater plankton in the experimental media. Supporting parameters observed were temperature, pH, dissolved oxygen, salinity, ammonia, and C / N and N / P ratio of water. Commercial probiotics are given every 7 days at a dose of 2 mg / l. The results showed that the treatment of different commercial probiotics resulted in differences in diversity, density and plankton dominance. The highest diversity index value (H ') obtained in probiotics A was 6.85 (moderate diversity), and dominance (C) was 0.96, meaning that there was dominant plankton, Chlorella sp. and Oscillatoria sp. whereas the highest plankton density was obtained in probiotics B at week 1 of 5.98x106 ind / ml.